Age- and sex-specific prevalence of chronic comorbidity in adult patients with asthma: A real-life study - Veenendaal, Mathijs (NPJ Prim Care Respir Med, 2019)
The presence of comorbidity can be associated with poorer asthma outcomes. Previous prevalence studies focused on a limited selection of comorbid conditions in asthma only. We aimed to determine age- and sex-specific prevalence estimates for the full range of chronic comorbid conditions in adult asthma patients by performing a retrospective cohort study based on 32,787 medical records of patients aged ≥16 years with asthma from 179 general practices in the Netherlands. Age- and sex-specific prevalence estimates of 76 chronic comorbidities and 14 disease categories based on International Classification of Primary Care codes were determined. Chronic comorbidity was present in 65.3% of male asthma patients and 72.8% of female asthma patients, with female patients having a higher mean (SD) of 2.0 (2.1) comorbidities compared to male patients (1.7 (2.0)). This mean increased to 5.0 (2.7) conditions in the 75+ age group. Most prevalent comorbidities were hypertension (20.1%), osteoarthritis (11.5%), eczema (11.5%) and dyspepsia (10.7%). Compared to male asthma patients, female asthma patients showed higher odds for the presence of other chronic conditions in eight disease categories. Neurological (odds ratio [OR]; 95% confidence interval 2.01; 1.76–2.29), blood forming/lymphatics (OR 1.83; 1.38–2.42) and musculoskeletal diseases (OR 1.82; 1.69–1.95) showed the highest association with female sex. In conclusion, the presence of chronic comorbidity is the norm in adults with asthma and it is more prevalent in female than in male asthma patients. The odds of having a specific comorbid condition may differ between the sexes. Attention in guidelines on how to handle comorbidities may lead to a more targeted treatment for comorbidities and more patient-centred asthma management.